Simulation and Experimental Study of Terahertz Wave Transmission Characteristics Based on Periodic Metal Open Resonant Ring Structures - Ren, Yunpeng; Li, Zhiyu; Chen, Yan; Ye, Yunxia; Xin, Zhiduo; Lu, Heng; Wan, Hanyu; Yao, Jianquan (International Journal of Optics, 2021)
Different open resonant ring structures with substrate of polyimide were designed. The transmission characteristics of the structures for terahertz wave were investigated by simulation and experiment. The results show that the transmission peak of the structures moves to high frequency with increase of thickness of the metal layer. With increase of substrate thickness, the transmission peak moved to low frequency and the transmissivity decreased. The influence of number of “C” shape open resonant rings in the unit structure on the transmission characteristics of terahertz wave was also studied. It is found that when the number of “C” shape open resonant rings increases from one to two, more transmission peaks appeared in the frequency of 0.2–2 THz. The transmissivity of the designed structures was tested by terahertz time-domain spectrometer (THz-TDS). The experimental results showed good agreement to the simulation results.